Adaptation and Psychometric Evaluation of the Feedback Orientation Scale Among Indonesian Employees - Andry Yanti; Anjani Arum Safitri; Fitria Rahayu; Aneuke Yu’dzia M; Mutiara Vinanda; Deni Agung Wicaksono; Agung Wicaksono; Sofi Nurul; Christiany Suwartono (Yayasan Sembilan Pemuda Indonesia, 2026)
The growing use of performance feedback systems in Indonesian organizations has increased the need for valid instruments that can assess how employees respond to feedback. However, validated Indonesian-language measures of employees’ receptivity to feedback remain limited. This study aimed to adapt and validate the Feedback Orientation Scale (FOS) for use in the Indonesian employee context. The FOS assesses an individual’s general tendency to receive, value, use, and feel accountable for feedback through four dimensions: Utility, Accountability, Social Awareness, and Feedback Self-Efficacy. The adaptation process followed the International Test Commission Guidelines for Translating and Adapting Tests and included translation, expert review, readability testing, item analysis, reliability testing, exploratory factor analysis, and confirmatory factor analysis. A total of 326 employees from various organizations in Indonesia participated in the study. Item analysis showed that one negatively worded item in the Accountability dimension had a low item-rest correlation and was therefore removed. The final Indonesian version consisted of 19 items. The psychometric findings indicated that all retained items demonstrated adequate item discrimination and that the four dimensions showed satisfactory internal consistency. Confirmatory factor analysis further indicated that the original four-factor structure provided a better fit than the alternative two-factor model identified through exploratory analysis. Overall, the adapted Indonesian FOS demonstrated acceptable validity and reliability for assessing feedback orientation among employees. The findings support the use of the 19-item Indonesian FOS in research and organizational practice, particularly in studies and interventions related to performance management, coaching, employee development, and feedback-based learning in diverse Indonesian workplaces.